2008
DOI: 10.1093/ndtplus/sfn165
|View full text |Cite
|
Sign up to set email alerts
|

Familial clusters of ANCA small-vessel vasculitis

Abstract: Small-vessel vasculitides associated with the presence of antineutrophil cytoplasmic antibodies in the serum are characterized by inflammation and necrosis of small vessels. A pauci-immune necrotizing crescentic glomerulonephritis typically occurs when there is renal damage. Pathogenesis of these diseases remains unclear although infectious, genetic and environmental factors have been involved. Few familial clusters of antineutrophil cytoplasmic antibodies’ small-vessel vasculitis are described in the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In the latter study, genotyping was performed but no HLA association was found between the siblings. In addition, Hay et al 5 reported a brother and sister with GPA both with renal manifestations, and Gomes et al 6 described the case of siblings who presented at the ages of 59 and 72 years with pulmonary and renal involvement. Gomes et al 6 also reported the cases of a father and daughter with GPA who presented with renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter study, genotyping was performed but no HLA association was found between the siblings. In addition, Hay et al 5 reported a brother and sister with GPA both with renal manifestations, and Gomes et al 6 described the case of siblings who presented at the ages of 59 and 72 years with pulmonary and renal involvement. Gomes et al 6 also reported the cases of a father and daughter with GPA who presented with renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hay et al 5 reported a brother and sister with GPA both with renal manifestations, and Gomes et al 6 described the case of siblings who presented at the ages of 59 and 72 years with pulmonary and renal involvement. Gomes et al 6 also reported the cases of a father and daughter with GPA who presented with renal disease. In a large population-based study, Knight et al 7 found that only 2 of 6670 first-degree relatives of patients with GPA and 13 of 68 994 population controls contracted the disease, giving a relative risk of 1.56 (95% CI 0.35 to 6.90).…”
Section: Discussionmentioning
confidence: 99%
“…A family reported by Gomes et al . [ 8 ] includes a father and daughter who both presented with renal disease; one was anti-PR3 positive and the other anti-MPO positive. Manganelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although very few cases of familial AAV have been reported, there have been various genetic studies including genome-wide association studies (GWASs) that have identified single nucleotide polymorphisms (SNPs) related to susceptibility. GWASs have also suggested some differences between the three AAV subsets or in geography [ 8 , 9 ]. A GWAS on United Kingdom patients revealed obvious genetic differences in GPA and MPA, and the genetic association was stronger in classification by ANCAs compared to classification by clinical presentation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%